ETHOLOGY OF SOME MEMBRACIDS ON ITS HOST PLANTS - RAJKUMAR, KRISHNAN; TENNYSON, SAMUEL; ARIVOLI, SUBRAMANIAN; VASSOU, MIRIAM (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
Membracids have received adequate attention for its taxonomic, habitual, behavioural and bioecological studies. In the present study, the behavioural aspects (feeding, communal life, resting, mimicry and colouration, oviposition, incubation, ecdysis, and parental care) of three membracids, viz., Leptocentrus taurus, Otinotus oneratus and Oxyrachis taranda on its host plants were studied by regular field observations at frequent intervals. The present study brought to light more salient behavioural features of membracids on its respective host plants. Hence, studies on other species of membracids exposed to different host plants may bring out additional behavioural aspects.